Mental Health, Work Stress, and Productivity: An Analysis of Punjab’s Industrial Workforce (Al-Qamar, 2025)
This study investigates the relationship between mental health, work stress, and productivity among industrial workers in Punjab, Pakistan, using a mixed-methods approach. Survey data from 399 workers reveal that 25.8% report poor mental health, while only 36.3% describe their mental health as good. Regression analysis demonstrates that workers with strong emotional control (23.3%) exhibit 1.8x higher productivity (Gamma = 0.593, *p* < 0.001), whereas those with poor stress management (43.1%) are 2.3x more likely to underperform (OR = 2.3, *p* < 0.01). Thematic analysis of managerial focus groups identifies inadequate institutional support as a critical stressor. The findings underscore a dose-response relationship between worsening mental health and declining productivity, with emotional regulation mediating 24% of this association. This study advocates for evidence-based workplace interventions, including employer-led mental health programs and policy reforms integrating psychological health into Pakistan’s occupational safety frameworks. By addressing systemic gaps in worker support, these measures could enhance both individual resilience and industrial efficiency in Punjab’s economically vital sectors.
Keywords: Industrial worker, mental health, Workplace stress, productivity, labor, Occupational health, Pakistan, Job stress